Distribution of Methylene Tetrahydrofolate Reductase Gene Polymorphisms in Women of Childbearing Age in Tai’an - Bo Zhou; Chengzhen Gao; Lirong Chen; Yumei Wang; Shufang Zhang; Chao Hou; Xiangyang An (International Journal of Genomics)
Conclusion: The MTHFR 677C > T and 1298A > C gene polymorphisms in Tai’an were obvious. About 87.6% of women of childbearing age were at medium or high risk of folic acid utilization.